THE EFFECTIVENESS OF VILLAGE FUND BASED (CASH FOR WORK) PROGRAMS IN RURAL INFRASTRUCTURE DEVELOPMENT (A STUDY OF NOELBAKI AND MATA AIR VILLAGES IN KUPANG TENGAH SUBDISTRICT) - Melania Andriani Astuti; Cicilia Apriliana Tungga; Rikhard T. C. Bolang (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the effectiveness of the Cash for Work program in infrastructure development in Noelbaki Village and Mata Air Village, as well as to identify the obstacles encountered during its implementation. The research employs a descriptive qualitative approach using the effectiveness measurement framework of Lubis and Huseini, which consists of the resource, process, and target approaches. Data were analyzed using NVivo 12 software. The results show that the implementation of the Cash for Work program in infrastructure development in Noelbaki Village is considered effective in terms of resources, process, and targets. This is reflected in the availability of funding sources, local labor, and adequate facilities and infrastructure, the implementation in accordance with the principles of the Cash for Work program, and the achievement of program objectives. Meanwhile, Mata Air Village is categorized as moderately effective. From the resource perspective, the availability of facilities and infrastructure is still inadequate, and from the process perspective, the self-managed (swakelola) principle has not been optimally implemented. The main obstacles identified in both Noelbaki Village and Mata Air Village include land acquisition issues from the community and delays in the distribution of materials to infrastructure development sites.